PEMODELAN ARSITEKTUR SISTEM INFORMASI PERIZINAN MENGGUNAKAN KERANGKA KERJA TOGAF ADM - Darmanto, Darmanto; Suyanto, Mohammad; Al Fatta, Hanif (Informasi Interaktif, 2018)
BPPTPM regency lamandau is a public service agency in the field of licensing, non-licensing and investment, is required to provide excellent service, trusted and transparent to the community. To achieve these objectives required appropriate strategies and utilization of information technology as a supporter in the work process. The objectives of this research are to identify the needs of services and business processes and to build an integrated information system architecture to support business activities at BPPTPM Lamandau District. Limitations of variables in this study are: This study uses input data from interviews, and document analysis in the form of renstra and renja BPPTPM and other documents required. The creation of a licensing information system architecture adopts the TOGAF ADM framework from the vision architecture phase to the technology architecture, as well as other methods such as PIECES Analysis, Value Cahin, SWOT, CSF, CUR Matrix, and SOA. The output of this research is blueprint information system without making application or prototype. The result of design of information system architecture using TOGAF ADM framework on business architecture using value chain analysis obtained 10 (ten) business functional areas, 5 (five) main business functions and 5 (five) supporting business functions. While the results of application portfolio mapping based on Mc Farlan obtained 9 (Nine) future information system which contains a collection of applications as a proposal to implement. As a guide in describing blueprint of licensing information system architecture at BPPTPM regency lamandau as a whole this research using TOGAF Foundation Architecture and SOA. Keywords :EnterpriseArchitecture, TOGAF,PIESCES, Value Chain.